ANALISIS TINGKAT KEPUASAN SISWA TERHADAP PROGRAM MAKAN BERGIZI GRATIS (MBG) DI SDN 3 HAURPANGGUNG - Pia Sopiah; Maulida Aulia Rahman; Rohani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of evaluating student satisfaction with the Free Nutritious Meal Program (MBG) in elementary schools, as students’ perceptions play a crucial role in determining the effectiveness of the program beyond mere food provision. The objective of this research is to analyze the level of student satisfaction with the MBG program at SDN 3 Haurpanggung. This study employs a quantitative descriptive approach with a survey design. Data were collected through questionnaires distributed to 91 students from grades IV, V, and VI, selected using random sampling based on the Slovin formula. The instrument used a Likert scale covering aspects such as taste, cleanliness, menu variation, portion size, and timeliness of food distribution. The data were analyzed using descriptive statistical techniques, including percentages and mean scores. The results indicate that the majority of students expressed satisfaction, with 63.74% categorized as satisfied and 18.68% as very satisfied, while no respondents reported dissatisfaction. The mean score of 3.63 reflects a generally positive perception of the program. It is recommended that future improvements focus on enhancing menu variation and food presentation, while further studies should examine the program’s impact on students’ nutritional status and academic outcomes.